Bridging Indigenous Knowledge and Cognition: A Metacognitive-Metaphor Learning Model to Enhance Mathematical Reasoning and Motivation - Demitra, Demitra; Herianto, Herianto (FKIP Universitas Lampung, 2025)
Students' obstacles in learning mathematics are due to weak reasoning and low motivation. This study aims to develop a metacognitive learning model using the metaphor of a rare Kalimantan tree to improve mathematics learning outcomes and motivation. The research method comprised the Recursive, Reflective, Design, and Development stages, with the learning model developed as a single-path prototype and validated through expert, small-group, and field validation. The instruments include expert assessments, student response questionnaires, mathematics achievement tests, and motivation scales. Data analysis used qualitative and quantitative descriptions, bar charts, line charts, and analysis of variance. The research findings are presented through the gradual development of the learning model from a single-path prototype to an alpha and beta version. The learning model, in the form of a single-path prototype, is a rough draft for organizing three components: metacognitive questions, metaphors, and hands-on activities. The alpha version of the learning model was developed through expert and small-group validation. Experts assess the learning model as very effective for mathematical reasoning and learning motivation, and easy to apply. The beta version of the learning model has been proven effective in improving mathematics learning outcomes and in the interaction effect between motivation and the learning model during the mathematics learning process. Teachers use it by creating worksheets with metacognitive questions and assigning hands-on activities. The results of this study contribute theoretically by highlighting elements of local wisdom as components of the model. Keywords: hands-on activity, mathematical reasoning, metaphor, metacognitive questioning strategy, motivation.